ENHANCING INNOVATOR SKILLS IN HIGHER EDUCATION IN INDONESIA - Ande, Diin Fitri (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2019)
Innovation plays important roles to survive in global economy. â€œinnovation has become an imperative for all advanced economies and a priority for a growing number of emerging countriesâ€(Forum, 2018). On the other hand, the Innovation performance of Indonesia relatively low, (rank in 87/126 in GII 2018, and rank 68 in GIC Report 2018). One factor that might contribute to that performance is the workforces in Indonesia do not have the skills, knowledge or health that are necessary to be innovation-driven (GII Report, 2017). On the other hand, the current educational system focuses more on academics sides without giving more opportunity for students to explore and to play. This paper aims to provide a proposition on how enhance the innovators skills in higher education in in Indonesia based on the work of Wagner (2012). This paper proposes the university to apply collaboration cultures, to have multidisciplinary learning, to encourage thoughtful risk-taking, trial and error culture, to encourage creating knowledge cultures, and to develop intrinsic motivation through play-passion-purpose..